Cell-specific integration of nuclear receptor function at the genome - Everett, Logan J. (2013)
Nuclear receptors (NRs) encompass a family of regulatory proteins that directly couple small-molecule signalling to transcriptional regulation. Initial studies of specific NR targets led to a model in which NRs bind highly specific DNA motifs in proximal promoter regions and strongly induce gene transcription in response to ligand binding. More recently, genome-wide studies have added to the complexity of this classic model of NR function. In particular, binding of NRs at weaker or alternate motifs is common in the context of DNA assembled into chromatin, and ligand responsiveness varies at different NR target genes. Such findings have led to proposed modifications to the classic view of NR regulation, including the “assisted loading” model in which NRs assist in opening chromatin rather than compete for binding sites, and context-specific models in which genomic and epigenomic features influence the NR function locally at each binding site. Further elucidati on of these mechanisms will be particularly important for understanding cell-specific and ligand-specific functions of each NR. Emerging genomic technologies such as ChIP-seq and GRO-seq provide insights on a larger scale leading to deeper understanding of the complexities of transcriptional regulation by NRs.